2013
DOI: 10.4209/aaqr.2012.05.0122
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Carbon Dioxide Emission by Using Microbial Fuel Cells during Wastewater Treatment

Abstract: To explore the feasibility of simultaneous carbon reduction and energy saving/recycling during wastewater decolorization, this study used naturally-occurring microbes (e.g., Aeromonas and Klebsiella sp.) for dye decolorization as well as energy and materials recycling. These microbes were tested for capabilities of bioelectricity generation in parallel with dye treatment for simultaneous energy recovery. The supplementation of electron-shuttling mediators (e.g., aminophenols) significantly increased the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…We also found that total SOC concentration was significantly and positively correlated with soil salinity when data from the two paddy fields were combined in the analysis, which was in agreement with the findings of a previous study conducted in a natural wetland close to our study site [47]. A higher salinity in soils could suppress microbial activity [59,60], including the microbial-mediated production of greenhouse gases (e.g., CH 4 and CO 2 ) and their subsequent release into the atmosphere [61][62][63].…”
Section: Effects Of Waste Amendment On Soil Active Soc Fractions and supporting
confidence: 90%
See 1 more Smart Citation
“…We also found that total SOC concentration was significantly and positively correlated with soil salinity when data from the two paddy fields were combined in the analysis, which was in agreement with the findings of a previous study conducted in a natural wetland close to our study site [47]. A higher salinity in soils could suppress microbial activity [59,60], including the microbial-mediated production of greenhouse gases (e.g., CH 4 and CO 2 ) and their subsequent release into the atmosphere [61][62][63].…”
Section: Effects Of Waste Amendment On Soil Active Soc Fractions and supporting
confidence: 90%
“…The application of waste amendments was also found to increase the soil C:N ratio. A higher C:N ratio was typically associated with a lower N availability to microbes, which would suppress organic matter mineralization and CO 2 emissions while at the same time increase the stability of MBC and the sequestration of soil C [20,63]. The increase in total SOC concentrations in response to the addition of waste amendments might also be related to the changes in soil N concentrations.…”
Section: Effects Of Waste Amendment On Soil Active Soc Fractions and mentioning
confidence: 99%
“…The gypsum slag fertilization treatment increased soil SO 4 2− (Chen et al ., 2013), thereby increasing the rate of SO 4 2− reduction and its accumulation in the soil. Higher sulphide concentrations in soil can inhibit microbial activity and subsequently decrease CO 2 emissions (Chen et al ., 2013). The gypsum slag and silicate and calcium fertilizer treatments decreased CO 2 emissions, an effect also associated with increases in soil water content.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar amendment also increased the soil C:N ratio. Higher C:N ratios are associated with limited N availability, which impedes mineralization and stabilizes microbial biomass carbon (Revell et al ., 2012), thereby lowering CO 2 emissions (Chen et al ., 2013). In fact, decreases in the release of N and P from litter have been associated with sudden decreases in CO 2 emissions (Asensio et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our simulated acid rain was also rich in SO4 2-(76.4 µmol l -1 ), and an increase in SO4 2can increase the rate of SO4 2reduction and the accumulation of sulfide in the soil. High soil sulfide concentrations can inhibit microbial activity and consequently CO2 emissions (Chen et al, 2013). Acid rain can also inhibit plant growth, decreasing above-and belowground biomasses and ultimately plant respiration and CO2 emission.…”
Section: 1effects Of the Amended Treatments On Co2 Fluxmentioning
confidence: 99%